Bent multi-layer pipe

By using solid semiconducting or non-conducting aggregates to adjust dielectric heating, the multilayer pipe maintains its bent shape and barrier properties by evenly distributing heat across layers, addressing overheating issues and ensuring material integrity.

JP7618036B2Active Publication Date: 2025-01-20TI AUTOMOTIVE FULDABRUCK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023528644
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-16
Filing Date
2021-11-16
Publication Date
2025-01-20
Estimated Expiration
2041-11-16

AI Technical Summary

Technical Problem

Multilayer plastic pipes face issues with degradation of barrier properties and loss of bent shape after dielectric heating due to uneven heating and overheating of layers.

Method used

The solution involves using solid semiconducting or non-conducting aggregates in the layers to adjust dielectric heating, ensuring balanced heating and retention of bent shape by matching the absorption coefficients and conversion temperatures of the plastics, thereby preventing overheating.

Benefits of technology

The solution ensures that the multilayer pipe maintains its bent shape and barrier properties by evenly distributing heat across layers, preventing overheating and maintaining material integrity during dielectric heating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618036000026
    Figure 0007618036000026
  • Figure 0007618036000027
    Figure 0007618036000027
  • Figure 0007618036000028
    Figure 0007618036000028
Patent Text Reader

Abstract

The pipe (1) comprises at least one first layer (3) and a second layer (2), the first layer (3) comprising a first plastic K1, the first plastic K1 having a conversion temperature T UK1 The second layer (2) includes a second plastic K2, which has a conversion temperature T UK2 The first layer (3) comprises aggregates Z, which are different from a polymer or copolymer. The aggregates Z are preferably solid, the solid being a semiconductor or non-conductor, and the aggregates Z promote dielectric heating of the pipe.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to European Patent Application No. 20207866.3, filed November 16, 2020, which is incorporated herein by reference.

[0002] The present disclosure relates to a pipe comprising at least one first layer and one second layer, the first layer comprising a first plastic K1 and the second layer comprising a second plastic K2, the first layer comprising an agglomerate Z, the agglomerate Z being solid and comprising little or substantially no polymers or copolymers, the agglomerate Z facilitating dielectric heating of the first layer and the pipe. [Background technology]

[0003] For example, such multi-layer plastic pipes are known from DE 69613130T2. As a result, aggregates such as water and softeners are used to achieve sufficient dielectric heating of the plastic material upon high-frequency excitation. For the pipes, minimum values ​​are recommended for the relative permittivity εr and the loss factor d, which ensures that the dielectric heating and thus the bendability of the pipe is sufficiently large in the region of the pipe's bending points.

[0004] From EP 1 182 345 A1, EP 2 476 938 A1 and EP 1 452 307 A1 multi-layer plastic pipes are known in which individual or several layers are provided with aggregates, for example the aggregates may contain electrically conductive carbon black or graphite fibres. Summary of the Invention [Problem to be solved by the invention]

[0005] However, it has been found that one of the problems encountered during the development of multi-layer pipes using aggregates is that in some cases the pipe loses certain desirable properties after dielectric heating. For example, the barrier properties of the barrier layer may be partially or completely degraded, which can be easily verified by pre- and post-testing. In other cases, it should be noted that the pipe does not retain its bent shape after dielectric heating.

[0006] Therefore, one of the objectives of the present disclosure is to provide a multi-layer pipe that has good material properties and can conveniently retain its bent shape even after dielectric heating. [Means for solving the problem]

[0007] To achieve the above object, the present disclosure provides a conversion temperature T UK1 At least one first layer having a first plastic K1 having an aggregate Z different from a polymer or copolymer, and a conversion temperature T UK2 and at least one second layer comprising a second plastic K2 having the

[0008] According to a further aspect, the imaginary part of the relative permittivity, normalized by the electric field constant and assigned to the first plastic K1, is the absorption coefficient A K1 and the imaginary part of the relative permittivity assigned to the second plastic K2 normalized by the electric field constant is the absorption coefficient A K2 and the imaginary part of the dielectric constant assigned to the aggregate Z, normalized by the electric field constant, is the absorption coefficient A Z and the absorption coefficient A S1 is assigned to the first layer (3), and the absorption coefficient A S2 is assigned to the second layer (2), and the absorption coefficient A K1 and the absorption coefficient A Z However, depending on the mixing ratio in the first layer (3), the absorption coefficient A S1 and jointly determining the absorption coefficient A of the second plastic K2. K2 is at least the absorption coefficient A S2 jointly determine the absorption coefficient AZ is the absorption coefficient A K1 Greater than.

[0009] Preferably, the aggregate Z is a solid, said solid being a semiconductor or a non-conductor.

[0010] The term "semiconductor" refers to a material having an electrical conductivity of preferably at most 104 S / cm. The electrical conductivity of a semiconductor is preferably and advantageously at least 10 -8 The electrical conductivity of a conductor is expediently higher than that of a semiconductor, and the electrical conductivity of a non-conductor is expediently lower than that of a semiconductor.

[0011] Preferably, the solid is in a solid agglomerate state and therefore is neither a liquid nor a gas at 20° C. The solid preferably has a melting point or decomposition temperature higher than that of the first plastic.

[0012] In particular, the term "layer" refers to a single layer of the pipe wall, meaning that the pipe wall has multiple layers arranged in a radially inner to outer direction. The layer is preferably made of homogeneously mixed materials and has one material component or multiple material components. The layer expediently preferably comprises at least one plastic, suitably the plastic being provided with an aggregate. The term "plastic" preferably refers to individual polymers, copolymers and / or polymer blends.

[0013] Conversion temperature T UK1 and T UK2 With regard to the melting point T, the latter corresponds to the corresponding melting point or decomposition temperature of each plastic minus room temperature 20°C (TR). SK1 For thermoplastics K1 the following formula applies:

number

[0014] For thermosetting or non-thermoplastic plastics, the conversion temperature T UK corresponds to its decomposition temperature minus 20°C.

[0015] The definitions of the "electric field constant" ε0, the "relative permittivity" εr and other electrical quantities are preferably interpreted in the sense of the standard specification of the German Electrotechnical Commission (DKE-IEV) (60050: edition of October 1, 2019). As a result, the complex permittivity can be written as follows:

number

[0016] Here, the complex permittivity ε can be normalized via the electric field constant ε as follows:

number

[0017] where εr' is the real part of the dielectric constant, also often called the dielectric constant k'. However, the term "constant" is not entirely accurate, since k' depends not only on the material but also on frequency and temperature. The imaginary part of the dielectric constant εr" is often called "dielectric loss" and is explained in more detail below.

number

[0018] Here, δ represents the angle between the imaginary and real parts, and is called the loss angle. In English-speaking countries, the dielectric loss factor d is often called the "loss tangent" or "dissipation factor".

[0019] It is common to express the dielectric properties of materials in terms of the real part of the relative permittivity εr' on the one hand, and the dielectric loss factor d on the other hand. The relative permittivity εr' indicates the proportion of electromagnetic radiation coupled into each material, while d represents the proportion of the coupled radiation absorbed in the material. The result is the product of these two quantities, i.e.

number

[0020] Therefore, the dielectric heat loss εr″ is proportional to the amount of heat coupled and absorbed. Its characteristics are:

number

[0021] Here, E2 represents the square of the electric field strength, and ω represents the circular frequency. The capital letter P represents the power dissipation, V represents the volume of the dielectric material, and the small letter p represents the power density. Here, an electric field is generated by an electromagnetic radiation source. For example, its circular frequency ω and electric field strength E are very important parameters in determining the power dissipation P, and are much more important.

[0022] On the other hand, the dielectric losses εr″ and ε″ are by far the more important parameters in materials and pipes and, when considered separately, are more informative with respect to heat losses in dielectric materials than the real part of the dielectric constant εr' and the dielectric loss factor d.

[0023] For example, the dielectric parameters ε' and ε" can be determined by an oscillatory circuit arrangement, in which a measuring capacitor is arranged in addition to a coil with fixed inductance L. The former is designed to accommodate the dielectric sample, and by measuring the resonant frequency and the quality of the oscillatory circuit, ε' and ε" can be determined. Furthermore, there are many other commonly known measurement methods, which differ notably in terms of the measurement technique and the spectrum of measurable ε'(ω) and ε"(ω).

[0024] ε' and ε" are frequency and temperature dependent and any desired time can be spent measuring either of these parameters. Therefore, here only ε" is determined at 25 °C and 10 MHz (a frequency that is within the spectrum of dielectric heating) and, for typographical simplicity, the material-dependent absorption coefficient A is defined as follows:

number

[0025] As a consequence, all values ​​of the absorption coefficient mentioned here relate to values ​​at 25°C and 10 MHz or 107 Hz, in particular to ensure comparability with values ​​from the literature. In this respect, as a standard reference, reference is made to "DIELECTRIC MATERIALS and APPLICATIONS" by R. von Hippel (Wiley Verlag, 1954). In the numerical table disclosed there, the two values ​​εr' = εr' / ε0 and tan δ = εr" / εr' at 25°C and 107 c / s (=107 Hz) are multiplied together to obtain the material-dependent value εr"(25°C, 10 MHz) = A.

[0026] However, it is often difficult, if not impossible, to separate the plastics K1 and K2 from the aggregate Z, and it is difficult to ensure that the dielectric properties of the plastics K1 and K2 are not altered during liquefaction and separation. However, the plastics of the first layer sample can be completely removed, e.g., by incineration or melting, while the dielectric properties of the aggregate Z remain unchanged. The absorption coefficient A Z Measurement of absorption coefficient A S1 Measurement of the weight of the plastic part G K1 and the weight fraction G of aggregate Z Z By measuring the mixing ratio of K1 can be determined as follows:

number

[0027] Here, the weight portion G K1 and G Z are dimensionless quantities that sum to 1. G K1 and G Z is determined by the weight of the first layer sample before removing the plastic K1 and the weight of the remaining aggregate Z. For the second layer sample, A K2 A similar procedure can be followed to determine A. After transformation of the previous equation, K1 can be calculated as follows:

number

[0028] This results in the absorption coefficients A S1 and A S2 The absorption ratio AV S can be determined.

number

[0029] Here, A S1 and A S2 In determining A, samples of each layer material (plastic and possible aggregates) are examined. S1 is produced by mixing plastic K1 with aggregate Z, which has an absorption coefficient A Z It has a very high absorption coefficient A Z A small amount of aggregates Z with a first layer absorption coefficient A S1 could have a decisive impact on

[0030] For example, the absorption coefficient A of the first plastic K1 K1 and the absorption coefficient A of the second plastic K2 K2 If the ratio is formed from the absorption ratio AV K is referenced.

number

[0031] The present disclosure is based on the understanding that individual layers can be heated so strongly during dielectric heating that they literally burn. For example, this can greatly impair the barrier performance of barrier layers. These layers often have a low melting point and are therefore relatively sensitive to heat. In contrast, heat-resistant layers have a high melting point and require more energy relative to mass to form a permanent bend.

[0032] Furthermore, many compromises have been found to be insufficient or even disadvantageous with regard to the thermal energy absorbed in the pipe. In the case of an unfortunate compromise, heat-sensitive layers may burn and the bending of the heat-resistant layer may not adapt to the desired shape due to insufficient heating. During the bending process, microcracks may form at the bending points of the heat-resistant layer in the case of insufficiently heated layers. Thus, one of the important findings of the present invention is that the layers need to be matched to each other in terms of dielectric heating, and that simply increasing the amount of heat absorbed by the layer, as described in DE 69613130 ​​T2, is not sufficient.

[0033] Furthermore, it was found that even the heat-resistant layers of newly developed pipes (e.g. polyamide) unexpectedly melt during dielectric heating. What was surprising was that the dielectric energy absorption was so well matched that practically no overheating should occur. This finding is based on the knowledge that electrically conductive materials (e.g. conductive soot) cause strong overheating of the corresponding layers, significantly exceeding purely dielectric heating.

[0034] Similarly, it has been found that in many, if not all, fabric softeners significantly increase conductivity. Fabric softeners (including water) are often semiconducting or non-conducting materials, and even liquids, that increase conductivity by increasing the mobility of ions. According to the present invention, only solids are considered as aggregates.

[0035] In contrast, the use of the aggregates Z as a solid semiconductor or non-conductor according to the invention has the effect of avoiding or significantly reducing the effects of overheating due to too high electrical conductivity. As a result, heating is essentially limited to dielectric absorption, which can be very well regulated by the semiconductor or non-conductor solid.

[0036] The invention is further based on the knowledge that the dielectric absorption of a multi-layer pipe consisting of n layers can be adjusted in two or three ways: In the first case, the dielectric absorption of at least two layers is adjusted to each other and preferably also to the respective melting points via at least one agglomerate, so that in the first case, all layers are softened to a similar extent within the same time during dielectric heating.

[0037] In the second case, not all layers are softened in the same way in the same period of time. For example, given n layers, only layers n-1, n-2, n-3, n-4 or less are added with a single aggregate Z or different aggregates Z, X, Y. Preferably only layers with aggregates Z, X, Y are heated sufficiently in a short time to soften their plastic sufficiently to be able to undergo a permanent bending deformation. In the first subcase, these layers are further thick or mechanically stable enough to hold the entire pipe in the bent shape, especially the layers that generate too little heat or soften too little.

[0038] In the second subcase, the layer containing the aggregates is not thick enough to sustain the bending deformation, but instead the dielectric heating lifetime is set large enough to ensure that the layer containing the aggregates is exposed to dielectric heating for a longer time than is actually necessary, so that a sufficient amount of thermal energy is radiated to the other layers to soften sufficiently.

[0039] These two cases or three subcases require precise adjustment of the dielectric heating, which, according to the invention, is a semiconducting or non-conducting solid with an absorption coefficient A Z A K1 This is achieved by the aggregate Z being larger than

[0040] Particularly preferred is a pipe with a longitudinal electrical conductivity of 10 -8 S / m or less than 10 -9 S / m or less than 10 -10 S / m or less than 10 -11 The electrical conductivity at both ends of the pipe is preferably less than S / m. To determine the electrical conductivity at both ends of the pipe, contact is preferably made over the entire surface of each end. Since the units of electrical conductivity have a length scale, short sections of 10 mm or 1 mm can be cut from the pipe and measured. Since the pipe cross-sectional area is constant, the values ​​obtained in units S or Ω can be easily converted to lengths of 1 m and units of S / m. The cuts are conveniently made perpendicular to the pipe axis and are preferably smoothed by grinding or a similar procedure. Preferably, the layers of the pipe represent parallel circuits of different resistors. The electrical conductivity of the pipe along its length is usually determined by said parallel circuits, especially based on the most electrically conductive layers.

[0041] Particularly advantageous is the absorption coefficient A Z is the absorption coefficient A S2 Or A K2 The absorption coefficient A Z A S2 Or A K2 Preferably, the thickness is at least 1.5 times, at least 2 times, at least 2.5 times, or at least 3 times greater than the thickness of the first layer, which is used to electrically tune each layer.

[0042] To align the layers, the absorption coefficient A S2 Or A K2 A K1 It is highly advantageous for the absorption coefficient A S2 Or A K2 A K1 It is desirable for the value to be at least 1.5, 2, 2.5, or 3 times greater than the value of

[0043] It is highly preferred that the plastic K1 of the first layer comprises a polymer selected from one of the following polymer classes: aromatic polyamides (PA), aliphatic polyamides (PA), partially aromatic polyamides (PA), polyesters (PES), polyetherketones (PEK), ethylene-vinyl alcohol copolymers (EVOH), fluoropolymers (FP), polyvinylidene chloride (PVDC), polyphenylene sulfide (PPS), polyurethanes (PU), thermoplastic elastomers (TPE), polyolefins (PO). On the other hand, the plastic K2 of the second layer is preferably selected from another polymer of the above-mentioned polymer classes. The background to this consideration is the fact that polymers of particularly different polymer classes require dielectric tuning.

[0044] The pipe may have a further layer or layers made of plastic. The further layer or layers preferably have an aggregate Z. The plastic of the further layer or layers advantageously comprises a polymer from the polymer class of plastic K1. It is particularly preferred that the plastic K1 is the same polymer as the further layer or layers. The first layer and the layer or layers may have the same plastic K1. The second layer may be arranged between the first layer and the at least one further layer. The further layer may be enveloped in the second layer or may envelop the second layer. The further layer may be in contact with the second layer. In the further layer or layers, the aggregate Z has the same weight fraction G as the first layer. Z may constitute.

[0045] It may be advantageous for the first layer to contact, encase and be encased in the second layer. The first layer is expediently adjusted to the second layer with respect to dielectric heating and softening, so that no aggregates are required in the second layer. Bonding between the layers is particularly important in the second case or the second and third subcases, where heat is dissipated from the first layer.

[0046] In some cases it is possible, preferably, that the second layer is free of solid, non-conductive or semi-conductive aggregates. There may be another layer in the pipe, consisting of a plastic that does not contain solid, semi-conductive or non-conductive aggregates. The plastic of the other layer or layers is preferably composed of a polymer from the polymer class of plastic K2. It is further preferred that plastic K2 has the same polymer as the other layer or layers. The second layer and the other layer or layers may comprise the same plastic K2. The absorption coefficient A of the second layer K2 is advantageously greater than the absorption coefficient of the remaining layers of the pipe.

[0047] Preferably, the first plastic K1 and the second plastic K2 are thermoplastic. This allows the conversion temperature T UK1 and T UK2 is expediently dependent on the associated melting point. Preferably, the conversion temperature (first conversion temperature) T UK1 The conversion temperature (second conversion temperature) T UK2 Define the conversion temperature ratio UV divided by A K1 A K2 The value divided by this is the absorption ratio AV K Define and convert temperature ratio UV to absorption ratio AV K The value divided by this is the main ratio HV K Therefore, the following formula is applied:

number

[0048] Here, the difference coefficient UF K is the main ratio HV K Based on this, it is determined according to the following formula:

number

[0049] A S1 A S2 The value divided by this is the absorption ratio AV S Define and convert temperature ratio UV to absorption ratio AV SThe value divided by this is the main ratio HV S When defining

number

[0050] Here, the difference coefficient UF S is the main ratio HV S Based on this, it is determined according to the following formula:

number

[0051] Here, inequality U satisfies the following equation.

number

[0052] If the main ratio HV is greater than 1, preferably, HV S or HV K and the respective difference coefficient UF between the value 1 K Or UF is determined, where each difference factor UF corresponds to a respective main ratio HV. Otherwise, each difference factor UF corresponds to the reciprocal of each main ratio HV. As a result, in the ideal case, the difference factor takes a value of 1, and the greater this value is, the worse it becomes.

[0053] It has been found to be very advantageous that, by adding aggregates Z, the individual layers are adjusted in terms of their individual heat absorption to their respective conversion temperatures TU or melting temperatures of the plastics of the respective layers. One very important finding is that this adjustment is preferably achieved by the addition of aggregates Z, so that the absorption ratio AV of the two plastics is S is sometimes done to approximate the conversion temperature ratio UV of the two layers. In this way, the heat of the dielectric heating is distributed evenly among several layers, so that the softening degrees of the first and second layers are close to each other. The difference coefficient UF SWhen is 1, the two layers soften to approximately the same extent, which results in a particularly fast and soft bending (first case).

[0054] Preferably, the difference factor UF S is at most 20, at most 10, further preferably at most 5, particularly preferably at most 2, very particularly preferably at most 1.5 and in the ideal case at most 1.2.

[0055] The pipe may have one or more additional layers of plastic, the additional layers being of weight fraction G Y The additional layer is made of aggregates Y having an absorption coefficient A Y is advantageously greater than the plastic of the respective additional layer. Preferably, the plastic of the additional layer or layers is different from plastic K1 and / or plastic K2. The plastic of the additional layer or layers preferably consists of a polymer different as far as possible from plastic K1 and / or K2. It is highly preferred that the polymer of the plastic of the additional layer or layers is selected from a different polymer class than plastic K1 or K2. It is particularly advantageous that the absorption coefficient A Y is the absorption coefficient A S2 Or A K2 The absorption coefficient A Y A S2 Or A K2 It is desirable for the ratio to be at least 1.5, 2, 2.5, or 3 times or more.

[0056] In particular, within the scope of the present disclosure, the layer or layers containing semiconducting or non-conducting solids, or the first layer or layers together with the other / other / further layer / layers, comprise 50% or more, or 70% or more, or 90% or more, or 95% or more of the weight of the pipe. The second layer or layers together with the other layer or layers may comprise less than 50%, or less than 30%, or less than 10%, or less than 5% of the weight of the pipe. Despite insufficient softening of the second layer, the mechanical stability of the first layer allows the bending process to be carried out in a short time, since the first layer holds the second layer in the bent shape (in the second case).

[0057] Advantageously, the inequality U is also satisfied at a temperature of 80° C., and preferably at 140° C. According to a preferred embodiment, the inequality U is also satisfied at an excitation frequency of 20 MHz, and advantageously at 40 MHz.

[0058] The second layer has aggregates X, in which a weight fraction G X may be assigned. Weight portion G X is determined relative to the weight of the second layer. S2 is applied to determine

number

[0059] So if the second layer has aggregate X, removing the plastic part will remove A. K2 can also be determined.

[0060] Aggregates Z and / or aggregates Y and / or aggregates X are in a particularly preferred case crystalline material. It is very advantageous if aggregates Z and / or aggregates Y and / or aggregates X are inorganic materials, preferably ceramic materials.

[0061] In particular, aggregates Z and / or aggregates Y and / or aggregates X may contain a metal oxide, which is preferably selected from the group "zinc suboxide, zirconium dioxide, titanium-containing metal oxides". The titanium-containing metal oxide may preferably be selected from the group "titanium dioxide, magnesium titanate, strontium titanate, barium titanate". However, aggregates Z and / or aggregates Y and / or aggregates X may contain molybdenum disulfide. Due to the high absorption coefficient of these materials, only small amounts need to be mixed into the layer, while the properties of the other layers remain largely unchanged.

[0062] According to a preferred embodiment, the absorption coefficient A Z and / or absorption coefficient A Y and / or absorption coefficient A X is preferably greater than 0.002, preferably greater than 0.005, more preferably greater than 0.01, more preferably greater than 0.02, even more preferably greater than 0.05, particularly preferably greater than 0.1, very particularly preferably greater than 0.15 or greater than 0.2. Z and / or absorption coefficient A Y and / or absorption coefficient A X It is advantageous for the absorption coefficient to be less than 100, more preferably less than 30, and especially less than 10. The advantage of a large absorption coefficient is that only a small amount of mixing of the individual aggregates is required, so that other properties of the individual layers are hardly changed. For large particles, excessively high values ​​of these absorption coefficients can cause localized micro-burns.

[0063] Weight fraction G for the first layer Z and / or weight portion G for additional layers Y and / or weight portion G for the second layer X It is preferred that the weight fraction G for the first layer is at least 0.0001, preferably at least 0.001, more preferably at least 0.01, and especially at least 0.1. Z and / or weight portion G for additional layersY and / or weight portion G for the second layer X is at most 0.5, preferably at most 0.3.

[0064] Preferably, aggregates Z and / or aggregates Y and / or aggregates X are in powder form. The average particle size of aggregates Z and / or aggregates Y and / or aggregates X is advantageously measured at most 500 μm, or 200 μm, or 100 μm, or 50 μm, or 20 μm, or 10 μm or less, which facilitates the production of the corresponding thin layers and ensures optimal heat distribution.

[0065] Preferably, the first or second layer is a barrier layer. According to a preferred embodiment, the second layer is a barrier layer. The material of the barrier layer preferably comprises a plastic selected from the group "EVOH, fluoropolymer, PPA, polyolefin, PVDC, TPE". In particular, EVOH, fluoropolymer, PPA or PVDC are preferred as the plastic of the barrier layer, with EVOH being most preferred. The barrier layer is preferably arranged between the innermost layer and the outermost layer. According to an embodiment, the second or barrier layer is the innermost layer. The barrier layer may form the innermost layer and preferably comprises a fluoropolymer.

[0066] It is possible for the pipe to consist of n layers, preferably at least n-1 layers each having at least one aggregate Z, Y, X. Advantageously, the layer j of the plastic having the largest absorption coefficient AKj is aggregate-free. In the case of more than one layer, the difference coefficient UF S or UF K UF Sij or UF Kij where i represents each layer different from layer j. All the difference coefficients UF Sij is preferably 20 or less, 10 or less, 5 or less, 2 or less, 1.5 or less, or 1.2 or less. Sij , advantageously all the difference coefficients UF Sij With respect to each of them, the associated differential coefficient UF KijIt is advantageous for the .gamma.

[0067] Within the scope of the present disclosure, the pipe may have at least one bending point, in particular at least two or three, particularly preferably at least four or five bending points. The pipe is preferably co-extruded and more preferably in one piece. In particular, the term "one piece" means that the pipe can only be divided into several pieces in a destructive manner.

[0068] The outer diameter of the pipe is expediently at most 30 mm, particularly preferably at most 20 mm. The wall thickness of the pipe is preferably between 0.1 mm and 5 mm, more preferably between 0.3 mm and 3 mm. The thickness of the first and / or second layer can measure in the range of 0.05 mm to 1.5 mm, particularly preferably between 0.1 mm and 0.5 mm.

[0069] In order to achieve the above object, the present disclosure recommends a fluid line comprising a pipe according to the invention, the fluid line having a line connector at each end of the pipe, at least one of the line connectors being reversibly connectable with a counterpart. The at least one line connector can advantageously be reversibly locked with the counterpart. Preferably, the at least one line connector comprises a female coupling. The coupling is expediently designed to receive the counterpart in a fluidly leak-tight manner. The counterpart is expediently configured as a male connector, preferably comprising a connector shaft and a collar or a groove encircling the connector shaft.

[0070] At least one line connector preferably comprises a retainer, which is preferably designed such that when the male connector is inserted into the combination, the retainer uses a peripheral collar / groove to lock the male connector into the combination. The retainer is preferably annular, in particular in the shape of an oval or circular ring, or is U-shaped in design. The retainer expediently comprises expanding arms, which preferably can expand elastically upon insertion of the mating part, and when the mating part is fully inserted, the arms use a peripheral collar / groove to lock the male connector into the combination.

[0071] The present disclosure will be described in more detail below with reference to the drawings, which merely show an example in a schematic manner. [Brief description of the drawings]

[0072] [Figure 1] FIG. 2 is a cross-sectional view of a pipe according to the present disclosure. [Diagram 2] FIG. 2 is a side view of a fluid line including the pipe of FIG. 1 and further including two line connectors in accordance with the present disclosure. [Diagram 3] FIG. 13 is a front view of the retainers disposed on each of the two line connectors. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0073] According to FIG. 1, the pipe 1 of the invention has three layers 2, 3, 4, the middle layer 2 being a barrier layer and containing EVOH. The outer layer 3 and the inner layer 4 each have polyamide 6, the polyamide 6 of the inner layer 4 being identical to the polyamide 6 of the outer layer 3. In this exemplary embodiment, the polyamide 6 may have an absorption coefficient of 0.1, while the middle layer 2 made of EVOH has an absorption coefficient of 0.6. The outer layer 3 made of polyamide 6 is understood as the "first layer" with the first plastic K1, while the middle layer 2 is understood as the "second layer" with the second plastic K2. In this exemplary embodiment, the inner layer 4 is understood as the "other layer" and also has the first plastic K1.

[0074] As a result, the absorption coefficient A K1 The value of is 0.1, while the absorption coefficient A K2 The value of T is 0.6. Both plastics K1 (PA6) and K2 (EVOH) are thermoplastics whose transformation points correspond to their melting points minus 20° C. In this exemplary embodiment, the transformation temperature T of polyamide 6 is UK1 is 200K (= 220° C-20°C), while the conversion temperature of EVOH is T UK2 may be 163K (=183°C - 20°C).

[0075] Due to its six times higher absorption coefficient and lower melting point, the dielectric heating heats the EVOH (second layer 2) to a temperature where it can be bent quickly. However, the two polyamide layers (first layer 3 and other layer 4) are not yet heated simultaneously enough to bend easily. If the pipe is heated further and the two polyamide layers are also heated to a temperature where they can be bent sufficiently, the middle layer will be heated so strongly that it will literally burn and lose most of its excellent barrier properties. In an exemplary embodiment, the main ratio HV K is calculated as follows:

number

[0076] Here, HV K >1, so the difference factor UF K also becomes 7.3.

[0077] According to the invention, the first layer 3 and the other layers 4 are mixed with aggregates Z, which are zirconium oxide (also called zirconia) in powder form. The aggregates Z are metal oxides, which exist in crystalline form and have an absorption coefficient A Z The value of 2 may be obtained. As a result, the aggregate Z has an absorption coefficient about 20 times larger than that of polyamide 6 and 3 times larger than that of EVOH. Zmay have a value of 10% or 0.1 for the two polyamide layers. As a result, the absorption coefficient A S1 The absorption coefficient ASW of the other layer 4 is calculated as follows:

number

[0078] Therefore, by mixing aggregate Z, the absorption coefficient A S1 and A SW increased by a factor of almost three. In contrast, the absorption coefficient A S1 is constant, so A K2 Therefore, the main ratio HV S The values ​​are as follows:

number

[0079] As a result, the difference coefficient UF S is the differential coefficient UF K Since inequality U is satisfied in the first layer 3, the same is true for the other layer 4 that is made up of the first layer 3, which may be made of the same material as the first layer 3 and thus derived from the same polymer melt source.

[0080] FIG. 2 shows the pipe 1 of FIG. 1 as a component of a complete fluid line 5. In this exemplary embodiment, besides the pipe 1 with the bend point 11, the fluid line 5 also includes two line connectors 6, each arranged at one end of the pipe 1. In this exemplary embodiment, the line connectors 6 are designed as female line connectors 6, which can receive a male counterpart 7. On the right side of FIG. 2, there is the male counterpart 7 as shown, which can be connected to a pipe (as shown) or to other components (pump, tank, etc.). The counterpart in this exemplary embodiment consists of a connector shaft 9 and a circumferential collar 10.

[0081] For connection with the counterpart 7, the line connectors 6 each have a coupling body 8 of female design, which is fixed to the pipe 1 by frictional forces or a material-to-material connection. For example, the material-to-material connection can also be designed as a laser welded seam. For example, a frictional connection can be established by a circumferential rib of the coupling body 8, into which the end of the pipe 1 is pressed. The coupling body 8 receives the connector shaft 9 of the counterpart 7, inside which there is preferentially an O-ring (not shown here) for sealing purposes.

[0082] Advantageously, the line connector and its associated counterpart 7 are reversibly connected to one another, ideally realizing a locking connection. To that end, a retainer 12 is pushed into the coupling body 8. The retainer 12 is preferably of U-shaped design (see FIG. 3). The retainer 12 has a head 14 as the base of the U and two arms 13 as the legs of the U. The arms 13 can be elastically spread by the collar 10 around the counterpart 7, so that after passing the collar 10, the two arms 13 again take their original position and the counterpart 7 is again locked in the coupling body 8. The two arms 13 can be spread by applying pressure to the head 14 and, by appropriately configuring the coupling body 8 accordingly, the counterpart 7 can be pulled out of the coupling body 8.

Claims

1. A first temperature T calculated based on the melting point and room temperature. UK1 At least one first layer having a first plastic K1 having an aggregate Z different from a polymer or copolymer, and a second temperature T calculated based on the melting point and room temperature. UK2 and at least one second layer comprising a second plastic K2 having A first coefficient A, in which the imaginary part of the relative dielectric constant assigned to the first plastic K1 is normalized by the electric field constant and calculated based on temperature and frequency K1 and A second coefficient A, in which the imaginary part of the relative dielectric constant assigned to the second plastic K2 is normalized by the electric field constant and calculated based on temperature and frequency K2 and The third coefficient A is calculated based on temperature and frequency and is the imaginary part of the dielectric constant assigned to the aggregate Z, normalized by the electric field constant. Z and The fourth coefficient A is calculated based on temperature and frequency. S1 is assigned to the first layer, and a fifth coefficient A is calculated based on temperature and frequency. S2 is assigned to the second layer, The first coefficient A K1 and the third coefficient A Z However, depending on the mixing ratio in the first layer, at least the fourth coefficient A of the first layer S1 jointly decide on The second coefficient A of the second plastic K2 K2 At least the fifth coefficient A of the second layer S2 jointly decide on The third coefficient A Z is the first coefficient A K1 Larger than The aggregate Z is a solid, the solid being a semiconductor or a non-conductor, and the pipe has an electrical conductivity in the longitudinal direction of less than 10 −8 S / m.

2. The third coefficient A Z is the fifth coefficient A S2 Or the second coefficient A K2 2. The pipe of claim 1, wherein the

3. The fifth coefficient A S2 is the first coefficient A K1 3. A pipe according to claim 1 or 2, characterized in that

4. 4. A pipe according to any one of claims 1 to 3, characterized in that the first plastic K1 of the first layer comprises a polymer selected from the following: aromatic polyamides (PA), aliphatic polyamides (PA), partially aromatic polyamides (PA), polyesters (PES), polyetherketones (PEK), ethylene-vinyl alcohol copolymers (EVOH), fluoropolymers (FP), polyvinylidene chloride (PVDC), polyphenylene sulfide (PPS), polyurethanes (PU), thermoplastic elastomers (TPE), polyolefins (PO), and the second plastic K2 of the second layer comprises another polymer selected from the above-listed polymer classes.

5. Further comprising one or more layers made of plastic, A pipe according to any one of claims 1 to 4, characterized in that the layer or layers comprise aggregates Z.

6. the first plastic K1 and the second plastic K2 are thermoplastic; the first temperature T UK1 the second temperature T UK2 The value divided by defines the temperature ratio UV, A K1 A K2 The value divided by is the ratio AV K Define The temperature ratio UV is the ratio AV K The value divided by this is the main ratio HV K Define the following equation: ##EQU00021## is applied, and the difference coefficient UF K is expressed as follows: [0022] Depending on the main ratio HV K is determined by A S1 A S2 The value divided by is the ratio AV S and the temperature ratio UV is defined as the ratio AV S The value divided by this is the main ratio HV S Define the following equation: [0023] is applied, and the difference coefficient UF S is expressed as follows: ##EQU00024## According to the main ratio HV S is determined by The inequality is, [0025] The pipe according to any one of claims 1 to 5, characterized in that

7. and further comprising one or more additional layers of plastic, The additional layer or layers may be in the form of a weight fraction G Y and an aggregate Y having 7. The pipe according to claim 1, wherein the aggregate Y is a non-conductive or semi-conductive solid.

8. A pipe according to any one of claims 1 to 7, characterized in that the first layer or layers having a semiconducting or non-conducting solid account for 50% or more, or 70% or more, or 90% or more, or 95% or more of the total weight.

9. The difference coefficient UF S 7. The pipe according to claim 6, characterized in that:

10. 10. A pipe according to any one of claims 1 to 9, characterized in that the aggregates Z and / or the aggregates Y are crystalline or metal oxides.

11. Aggregate Z and / or Aggregate Y are in powder form; A pipe according to any one of claims 1 to 10, characterized in that the average particle size of the aggregates Z and / or the aggregates Y is at most 100 μm.

12. 12. A pipe according to any one of the preceding claims, characterized in that the second layer of the plurality of layers is a barrier layer, the material of which comprises a plastic selected from the group consisting of ethylene-vinyl alcohol copolymers, fluoropolymers, polyphthalamides, polyolefins, polyvinylidene chloride, thermoplastic elastomers.

13. A pipe according to any one of the preceding claims, characterized in that it has at least one bending point.

14. A fluid line comprising a pipe according to any one of claims 1 to 13, The pipe has line connectors at both ends, At least one of the line connectors is adapted to reversibly connect to a mating fluid line.

Citation Information

Patent Citations

  • Piping member for fuel transportation

    JP2011169467A

  • Articles containing tubular particles

    JP2018517026A